Effect of equivalence ratio and staging ratio on the methane MILD combustion in dual-stage combustor. (1st January 2022) - Huang, Mingming; Li, Ruichuan; Xu, Jikang; Cheng, Shen; Deng, Haoxin; Rong, Zhiyu; Li, Yue; Zhang, Yanfei
Highlights: The reaction images for different equivalence ratio were shown. The OH* imges and NOx production in the MILD combustion zone were analyzed. The NOx reduction mechanism prevails over the NOx formation mechanism under MILD mode. Abstract: The effect of equivalence ratio and staging ratio on the CH4 MILD (Moderate or Intense Low-oxygen Dilution) combustion was examined in an axially staged MILD combustor. The results were presented on reactant temperature and dilution as well as the ignition delay time through CRN (chemical reaction network) calculation. Also, the data on the OH* radicals distribution and exhaust emissions were obtained using experiments. Higher staging ratio induces the high temperature low oxygen thermodynamic condition required for MILD scheme, yet reduces the ignition delay time. An expanded and downstream moved reaction region was observed at higher equivalence ratio. Reduced and even negative NOx emissions from the MILD combustion zone are acquired at high staging ratio, implying that the NOx reduction mechanism is superior to the NOx formation mechanism in the MILD combustion zone. The opposite effect of staging ratio on the CO emission for low equivalence ratio and high equivalence ratio is also observed. With primary air swirled in the primary combustion zone, the staged combustor exhibits an excellence performance with distributed reaction region and ultra-low NOx and CO emissions under gas turbine relevant lean operating condition.